An efficient approach for optimal sensor placement and damage identification in laminated composite structures. (May 2018) - Dinh-Cong, D.; Dang-Trung, H.; Nguyen-Thoi, T.
Highlights: An efficient approach for optimal sensor placement and damage identification in laminated composite structures is proposed. A modal reduction technique is adopted to develop a reduced order model for optimal sensor placement (OSP). The optimal sensor layout obtained from the OSP strategy is validated through a damage detection technique. The Jaya algorithm is found to be an efficient optimization tool for solving both discrete and continuous optimization problems. Abstract: This paper proposed an efficient approach for optimal sensor placement and damage identification in laminated composite structures. This approach first utilized a model reduction technique, namely iterated improved reduced system (IIRS) method, to develop a reduced order model for optimal sensor placement (OSP), and then the OSP strategy using Jaya algorithm is conducted by formulating and solving an optimization problem for finding the best sensor locations. The objective function of the optimization problem is defined based on the correlation between the flexibility matrix obtained from an original finite element model and the corresponding one calculated from IIRS method. Next, the approach uses the measured incomplete modal data from optimized sensor locations for detecting and assessing any stiffness reduction induced by damage. In order to do this, the damage identification problem is formulated as an optimization problem where the damage extent of elements and the modal flexibility change are taken as the continuous design variables and the objective function, respectively. The Jaya algorithm is again adopted to solve the optimization problem for determining the actual damage sites and extents. Numerical simulations of a three cross-ply (0°/90°/0°) beam and a four-layer (0°/90°/90°/0°) laminated composite plate are carried out to demonstrate the applicability and efficiency of the proposed approach.